Interdisciplinarity and virtuality in the academic dialogue of the virtual tribune : Rhetoric and communications e-Journal (Philology, 2023)
Мавродиева, Иванка, главен редактор. Реторика и комуникации. София: Институт по реторика и комуникации. ISSN: 1314-4464